The Influence of the LIPIRTUP Strategy on the Short Story Writing Skills of Class VII Students at SMPN 24 Medan - Sinaga, Magdalena Shinta; Siregar, Rosdiana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the effect of the LIPIRTUP strategy on the short story writing skills of class VII students at SMPN 24 Medan. The method used in this research is the one-group pre-test post-test design experimental method. Hypothesis testing was carried out using the